2018
DOI: 10.12659/ajcr.908000
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Ventriculitis and Meningitis Caused by Streptococcus Acidominimus in Humans: A Case Report

Abstract: Patient: Male, 49Final Diagnosis: Pyogenic ventriculitis and meningitis caused by Streptococcus acidominimusSymptoms: Confusion • fever • headacheMedication: —Clinical Procedure: AntibioticsSpecialty: Infectious DiseasesObjective:Rare diseaseBackground:Streptococcus acidominimus, which belongs to the viridans streptococci group, is rarely considered pathogenic in humans. However, over the past 10 years, this bacterium has been reported to cause serious infections in humans, particularly among the critically il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The most common pathogen were Streptococcus pneumonia and Hemophilus influenza (18). This result suggested that not all meningitis patients suffered from ventriculitis or CSF infection (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common pathogen were Streptococcus pneumonia and Hemophilus influenza (18). This result suggested that not all meningitis patients suffered from ventriculitis or CSF infection (7).…”
Section: Discussionmentioning
confidence: 99%
“…The ventricles are responsible for the circulation of CSF throughout the brain. Ventriculitis is caused by infection in the ventricles, leading to swelling and inflammation (7).…”
Section: Introductionmentioning
confidence: 99%